Membership Administration System & Online Service in Building the Quality of Service for the Customer Loyalty of Papaya Renon - Afrian Agung Setiawan; A.A.N Eddy Supriyadinata Gorda; Lusia Adinda Dua Nurak (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The era of Globalization with an increasingly advanced and technological civilization, requires that various sectors are expected to follow suit and take advantage of it. The government and private sectors are also adopting changes, as well as the evolving environmental demands of the industrial revolution 4.0 to further facilitate performance, increase productivity and more effective and efficient company operational activities. PT. Glory Retailindo is a company in the field of convenience good supply, utilizing technology in its operational activities, related to membership administration and online service. However, in its implementation, many problems occur, one of which is from the level of data integration and data updating (customer data updates) which are not optimal to the tracking and handover process of customer ordered goods which is still simple. Therefore, this study was conducted to find out how the membership administration system and online service papaya in building service quality and the impact of company service quality on customer loyalty. This research uses a descriptive qualitative approach method, where data can be obtained through observation, interviews, and documentation. The results showed that the implementation of the membership administration system and online service has not been optimally running, with a simple system, limited customer data storage space, handover and tracking of customer orders manually, so that the level of loss, data changes is either due to the influence of human error or system error. The quality of papaya fresh gallery service is upheld by the company both quality, speed, and product safety guarantees. The implementation of the membership administration system, online customer service needs to be improved and developed more optimally so that it is expected to be able to encourage the level of effectiveness and efficiency of the company.